2022
DOI: 10.1108/pijpsm-10-2021-0142
|View full text |Cite
|
Sign up to set email alerts
|

Towards inclusionary policing: a critical inquiry into the pre-trial treatment of suspects with intellectual disabilities in Ireland

Abstract: PurposeThis paper aims to critically evaluate contemporary Irish police practice, with an emphasis on emergent procedural innovations, in light of the needs of suspects with intellectual disabilities.Design/methodology/approachA review of published prevalence data in respect of people with intellectual disabilities in the Irish criminal justice system, of the Irish legal and policy landscape and the results of a recent empirical inquiry are used in critical evaluation.FindingsIn line with extant international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…To examine how police might influence the production of evidence for individuals with I/ DD, one of the articles in this special issue focuses specifically on the pre-trial phase when police produce evidence for cases by gathering information during police interviews with victims and suspects. In this special issue, authors Cusack et al (2022) found that people with intellectual disabilities encounter cognitive and communicative difficulties during their interviews with police, due to what the authors called their "psychological vulnerabilities". They explain that forensic questioning, done without accommodation for people with I/DD, can yield false confessions due to leading questions and stressful conditions that lead to increased anxiety for the individual.…”
Section: Inside Interactions Between the Police And Individuals On Th...mentioning
confidence: 99%
“…To examine how police might influence the production of evidence for individuals with I/ DD, one of the articles in this special issue focuses specifically on the pre-trial phase when police produce evidence for cases by gathering information during police interviews with victims and suspects. In this special issue, authors Cusack et al (2022) found that people with intellectual disabilities encounter cognitive and communicative difficulties during their interviews with police, due to what the authors called their "psychological vulnerabilities". They explain that forensic questioning, done without accommodation for people with I/DD, can yield false confessions due to leading questions and stressful conditions that lead to increased anxiety for the individual.…”
Section: Inside Interactions Between the Police And Individuals On Th...mentioning
confidence: 99%